PSpHT a Water Strider-like Robot for Water Inspection: Framework and Control Architecture - Addie Irawan, Hashim; Beh, Khi Khim; Tan, Yee Yin (2014)
This paper presents the framework and control of a proposed water strider-liked robot, named as Portable Striding pH Tester (PSpHT) that is able to measure the water quality. PSpHT is designed with its leg and tip configurations made respectively from the light-steel beam and polypropylene-based material. The design of the leg is calculated and fabricated using Archimedes' principle. In addition, real-time software for use in a remote controlled pH data logger that strides the robot, called PSpHT-VI, is developed using radio frequency (RF) communication. The PSpHT is verified and validated by running two specific tests, which are striding topology test and real-time data Potential Hydrogen (pH) reading test. The tests were conducted in a lake within the campus of the Universiti Malaysia Pahang, Pekan.